2003
DOI: 10.1124/jpet.102.046243
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Peptide Drugs to the Brain by Adenovirus-Mediated Heterologous Expression of Human Oligopeptide Transporter at the Blood-Brain Barrier

Abstract: The feasibility of using adenovirus-mediated human oligopeptide transporter (hPEPT1) gene transfer to achieve peptide drug delivery to the brain across the blood-brain barrier was tested by examining the accumulation of model peptides in a rat brain endothelial cell line (RBEC1) and rat brain after transduction with a recombinant adenovirus encoding hPEPT1-enhanced yellow fluorescent protein fusion gene (AdhPEPT1-EYFP). In vitro uptake of [ 3 H]GlySar was determined in RBEC1 transduced with AdhPEPT1-EYFP. In v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Toyobuku et al 86 examined the feasibility of heterologous transduction of a transporter gene to the BBB. As peptides have multiple biological actions in the brain, they are potentially valuable as neuropharmaceuticals in the treatment of various disorders, such as Alzheimer's disease and depression.…”
Section: Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Toyobuku et al 86 examined the feasibility of heterologous transduction of a transporter gene to the BBB. As peptides have multiple biological actions in the brain, they are potentially valuable as neuropharmaceuticals in the treatment of various disorders, such as Alzheimer's disease and depression.…”
Section: Peptidesmentioning
confidence: 99%
“…Delivery of peptide drugs to the brain, however, is a major challenge, because distribution of peptides to the brain is generally very low owing to the presence of the BBB. Toyobuku et al 86 constructed a recombinant adenovirus vector encoding PEPT1 and transduced the transporter into the BBB of rats by carotid artery injection of the vector. Heterologous expression of PEPT1 at the BBB successfully increased the brain distribution of a model substrate, cefadroxil, of PEPT1.…”
Section: Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Toyobuku et al [42] examined the feasibility of heterologous transduction of a transporter gene to the BBB. As peptides have multiple biological actions in the brain, they are potentially valuable as neuropharmaceuticals in the treatment of various disorders, such as Alzheimer's disease and depression.…”
Section: Peptides Transportmentioning
confidence: 99%
“…It has been reported that BCECs could secrete gene products into the brain parenchyma by a paracrine mechanism [1]. Additionally, the heterologous expression of oligopeptide transporters at the brain capillary endothelium has been found to be capable of delivering peptide drugs to the brain [2]. Therefore, it is of great significance to develop an effective method for gene transfer into BCECs.…”
Section: Introductionmentioning
confidence: 99%